EFFORTS TO IMPROVE NATIONALISM THROUGH HISTORY LESSON BY SOCIO DRAMA METHOD USAGE IN CLASS OF XII SOCIAL 2 MAN 2 JEMBER 2017/2018 ACADEMIC YEAR - Hilda Susanti; Nurul Umamah; Sri Handayani (JURNAL HISTORICA, 2018)
The purpose of learning history is to increase the nationalism of students. Teachers should facilitate students in order to gain the students’ nasionalism. The purpose of this research is to improve the students’ nationalism by using the method of socio-drama through the history lesson in class XII IPS 2 of MAN 2 Jember in 2017/2018 academic year. There were 30 students as the research participants. This research used Classroom Action Research (CAR). This research was started from February to November 2017. The results of this research found that there was an improvement of the students’ nationalism. The improvement of students’ Nationalism were shown from the indicator of nasinalism they were; love of the nation and the country, on pre-cyle= 67,16%, on the cyle I= 75%, and on the cyle II= 83,66%; awere have a nation is one nation of Indonesia, on the pre-cyle= 68.37%, on the cyle I= 74,48%, and on the cyle II= 83,14%; aware having state of Indonesia, on the pre-cyle= 70,23%, on the cyle I= 74,64%, and on the cyle II= 84,16%.Keywords: Socio-Drama Method; Nationalism; History Learning Outcomes